2014
DOI: 10.4172/0974-8369.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Vitamin E and Butylated Hydroxytoluene Antioxidant Function in Response to Paraquat-Induced Chromosomal Damage in Cultured Anuran Leukocytes

Abstract: Researchers have reported that the phenolic antioxidants vitamin E and butylated hydroxyltoluene (BHT) effect on cultured cells and human low-density lipoprotein is disrupted by various synthetic chemical compounds and Cu 2+ involved in reactive oxygen species (ROS) generation by redox reaction. In this paper, information involved in prooxidative action of vitamin E and BHT in cultured anuran leukocytes is provided in attempt to clarify such disruption mechanisms of antioxidant function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…In sheep, a small protective function related to thermal shock was reported ( Watson and Anderson, 1983 ), and the benefits of HB for sperm cryopreservation in sheep ( Farshad et al, 2010 ; Palomo et al, 2017 ) and other species ( Memon et al, 2011 ; Naijian et al, 2013 ; Merino et al, 2015 ) was demonstrated. Considering that cryopreservation increases the sperm sensitivity to oxidative stress ( Marti et al, 2008 ), the effects of HB may go further than thermal shock protection, as HB is a synthetic analogue of vitamin E, an inhibitor of lipoxygenase, and able to prevent oxidation of polyunsaturated fatty acids ( Bast et al, 1991 ; Hanada, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In sheep, a small protective function related to thermal shock was reported ( Watson and Anderson, 1983 ), and the benefits of HB for sperm cryopreservation in sheep ( Farshad et al, 2010 ; Palomo et al, 2017 ) and other species ( Memon et al, 2011 ; Naijian et al, 2013 ; Merino et al, 2015 ) was demonstrated. Considering that cryopreservation increases the sperm sensitivity to oxidative stress ( Marti et al, 2008 ), the effects of HB may go further than thermal shock protection, as HB is a synthetic analogue of vitamin E, an inhibitor of lipoxygenase, and able to prevent oxidation of polyunsaturated fatty acids ( Bast et al, 1991 ; Hanada, 2014 ).…”
Section: Discussionmentioning
confidence: 99%